2020
DOI: 10.4081/tz.2020.80
|View full text |Cite
|
Sign up to set email alerts
|

Blessing the rains down in Africa: spatiotemporal behaviour of the crested porcupine <em>Hystrix cristata</em> (Mammalia: Rodentia) in the rainy and dry seasons, in the African savannah

Abstract: The assessment of habitat selection and temporal patterns of activity rhythms is paramount for wildlife conservation. Studies on behavioural ecology of wild mammals are particularly challenging in tropical areas, mostly when involving rare or elusive species. Despite being a common species in Italy, the crested porcupine Hystrix cristata is threatened of extinction throughout most of its sub-Saharan range. All available information on the ecology of this species has been collected in Italy, whereas no data is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Similarly, Mori et al (2020) showed that the wild boar increases its nocturnality and reduces diurnal activity in areas where a high frequency of wolf passage was recorded. Our findings showing that wild boars are less active during very bright nights, lead us to interpret this behaviour as an anti-predatory strategy, similar to moonlight avoidance in small mammals (Viviano et al 2020;Hernández et al 2021). Thus, where hunting occurs, where predation pressure is high, or in suburban and urban areas, the onset of wild boar activity is usually recorded at sunset (Cahill et al 2003;Mori et al 2020;Rossa et al 2021), whereas in protected areas and where predators are rare, it may occur some hours before (Russo et al 1997;Podgórski et al 2013;Zanni et al 2021).…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, Mori et al (2020) showed that the wild boar increases its nocturnality and reduces diurnal activity in areas where a high frequency of wolf passage was recorded. Our findings showing that wild boars are less active during very bright nights, lead us to interpret this behaviour as an anti-predatory strategy, similar to moonlight avoidance in small mammals (Viviano et al 2020;Hernández et al 2021). Thus, where hunting occurs, where predation pressure is high, or in suburban and urban areas, the onset of wild boar activity is usually recorded at sunset (Cahill et al 2003;Mori et al 2020;Rossa et al 2021), whereas in protected areas and where predators are rare, it may occur some hours before (Russo et al 1997;Podgórski et al 2013;Zanni et al 2021).…”
Section: Discussionmentioning
confidence: 56%
“…To date, the crested porcupine is classified as "Least Concern" by the International Union for Conservation of Nature (IUCN) (Amori and De Smet 2016), despite being almost rare in Central African countries (Viviano et al 2020). Nevertheless, in spite of this classification, data referring to its population trend are still widely lacking (Amori and De Smet 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The crested porcupine H. cristata Linnaeus, 1758 is a large, nocturnal rodent which is widespread in North and sub-Saharan Africa [21][22][23]. It is the only porcupine species occurring in Europe, with a geographical distribution restricted to mainland Italy and Sicily, most probably due to its introduction from North Africa in the early Medieval period [24][25][26].…”
Section: Discussionmentioning
confidence: 99%